Balancing the scale of work and life / Norhidayah Ali and Azni Syafena Andin Salamat - Ali, Norhidayah; Andin Salamat, Azni Syafena (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
Work-Life Balance (WLB) is a term that describes the process of achieving a healthy balance between work and personal life. According to Lockwood (2003), WLB refers to the condition where employees strike a balance between both professional and personal obligations. A good WLB creates a productive and healthy environments both at work and at home. The context of a person's personal life may include time spent developing relationships and performing non-job duties, as well as time spent pursuing personal interests.